THE INFLUENCE OF NICKEL ACETATE NI(CH3CO2)2 CONCENTRATIONS ON THE OPTICAL PROPERTIES OF COMPOUND (ZINC OXIDE, ALUMINUM OXIDE) BASED ON EPOXY RESIN (Academia Science Repository, 2023)
Composite thin films are intentionally manufactured media that typically consist of two or three phases, one of which is metallic and the other dielectric. The word "thin films" denotes that it's about composites with a little amount of metal phase.